Peningkatan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Akidah Akhlak melalui Penerapan Metode Problem-Based Learning - Putri Lubis, Indriani; Astuti, Dewi (Ahdāf: Jurnal Pendidikan Agama Islam, 2024)
This study aims to investigate the impact of implementing the Problem-Based Learning (PBL) method on enhancing students' critical thinking skills in the subject of Islamic Ethics (Akidah Akhlak) at the eighth-grade level in Madrasah Tsanawiyah Negeri 1(MTsN 1) Kota Lhokseumawe. The context of this research is grounded in the need for a teaching method that not only develops intellectual intelligence but also addresses the spiritual, moral, and religious aspects of students. The research adopts a quantitative approach with an experimental research design. The study population comprises all eighth-grade students at MTsN 1 Kota Lhokseumawe, with the sample consisting of an experimental class applying the PBL method and a control class using conventional methods. Data collection involves questionnaires and observations, while data analysis employs homogeneity tests and hypothesis testing. The findings reveal that the implementation of the PBL method has a significant influence on the improvement of students' critical thinking skills. The average questionnaire score for the experimental class is 92.74, whereas the control class scores 82.65. Hypothesis testing indicates that the t-value (5.12) exceeds the critical t-value (1.675) at a 5% significance level. Therefore, the null hypothesis is rejected, and it can be concluded that PBL effectively enhances students' critical thinking skills compared to conventional methods. Based on these findings, it is recommended to further integrate the PBL method in the curriculum development of the Islamic Ethics subject. This recommendation can serve as a foundation for education policymakers and educators to design more adaptive, active, and relevant teaching strategies in response to the dynamics of modern education.